1994
DOI: 10.1001/jama.1994.03510320035026
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Patch Therapy for Smoking Cessation Combined With Physician Advice and Nurse Follow-up

Abstract: Objective.\p=m-\To determine the efficacy of a 22-mg nicotine patch combined with the National Cancer Institute program for physician advice and nurse follow-up in providing withdrawal symptom relief, 1-year smoking cessation outcome, and percentage of nicotine replacement.Design.\p=m-\Randomized,double-blind, placebo-controlled trial. Subjects.\p=m-\Two-hundredforty healthy volunteers who were smoking at least 20 cigarettes per day.Interventions.\p=m-\Basedon the National Cancer Institute program, subjects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…However, a prior study showed no evidence of withdrawal when smokers were taken off a nicotine patch (Hurt et al, 1994). Also, secondary analysis of data from two placebo-controlled patch studies of traditional design (Richmond et al, 1994;TNSG, 1991) confirmed our basic finding of better symptom relief on active patch, when more dependent smokers are examined.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, a prior study showed no evidence of withdrawal when smokers were taken off a nicotine patch (Hurt et al, 1994). Also, secondary analysis of data from two placebo-controlled patch studies of traditional design (Richmond et al, 1994;TNSG, 1991) confirmed our basic finding of better symptom relief on active patch, when more dependent smokers are examined.…”
Section: Discussionmentioning
confidence: 57%
“…Studies of the effect of NRT on symptoms beyond 6 weeks have been mixed, with some studies failing to find effects (Richmond, Harris, & de Almeida Neto, 1994;Russell et al, 1993;TNSG, 1991;Tonnesen et al, 1999;Westman, Levin, & Rose, 1993), and others reporting effects as late as week 10 (Abelin et al, 1989;Fiore, Kenford, Jorenby, Wetter, Smith, & Baker, 1994;Hurt et al, 1994). In general, clinical trials of patch vs. placebo are ill suited to address the question of effects after week 6.…”
Section: Introductionmentioning
confidence: 99%
“…Seven-day point prevalence and continuous abstinence at weeks 1, 3, 6, and 26. Secondarily, for 7-day point prevalence cessation, we also compared only those who returned regardless of their returning outside of their follow-up visit interval, and we treated those lost to follow-up as missing.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] In a previous study using 22-mg transdermal nicotine patch therapy for 8 weeks, we observed that the median percentage of cotinine replacement in abstinent subjects receiving active patch therapy was 54%, with only 25.5% of the subjects achieving greater than 100% replacement. 25 Low maintenance levels of percentage of re- …”
mentioning
confidence: 99%